132 The additional value of cardiopulmonary exercise testing over conventional treadmill testing in patients with moderate to severe aortic stenosis. (May 2019) - Badiani, Sveeta; van Zalen, Jet; Hart, Lesley; Topham, Ann; Armado, Karen; Monteiro, Ricardo; Hoare, David; Althunayyan, Aeshah; Borikan, Sahar; Marshall, Andrew; Bhattacharyya, Sanjeev; Patel, Nik R; et al.
Abstract : Introduction: Current guidelines recommend aortic valve replacement in patients with apparently asymptomatic severe aortic stenosis, who exhibit symptoms or a decrease in blood pressure on exercise testing. However, the additional information provided by cardiopulmonary exercise testing (CPET) is limited. This study sought to establish the additional information provided by CPET in this context. Methods: An analysis of patients with aortic stenosis undergoing CPET in an enhanced valve surveillance clinic was performed. Symptom limited cardiopulmonary exercise testing with respiratory gas exchange analysis was used, and the patients were encouraged to exercise until exhaustion. Results: 71 patients with moderate to severe aortic stenosis and good left ventricular function (AVVmax 4 0.5m/s MG 38 11mmHg, AVA 0.9 0.2cm 2, LVEF 60 8%)were included in the analysis. The mean age was 74.2 12.1 years and 51 patients (70.4%) were male. 33 (46.5%) patients had a background of hypertension, 12 (16.9%) had diabetes mellitus and 8 (11.3%) had coronary artery disease. All patients denied cardiovascular symptoms at baseline. A total of 119 CPETs were performed. All patients exercised to respiratory exchange ratio (RER) >1.1 indicating good effort. Of the 71 patients, 26 (37%) exhibited a peak VO2 <84% predicted. 11 patients (15.5%) developed breathlessness on exertion, 7 (9.9%) exhibited a fall in blood pressure below baseline and 3 (4.2%) developed ST depression. 18 patients (25.3%) had a peak VO2 <84% predicted, but without symptoms, fall in blood pressure or ST depression. There was a significant correlation between peak VO2 and AVA (r= 0.24, p= 0.047, but not between peak VO2 and transaortic velocity (r=0.117, p=0.339) and peak VO2 and mean gradient (r=0.139, p= 0.256). Over a median follow up time of 8 months (IQR 4 to 28 months), 28 patients (39%) were referred for aortic valve intervention. There were 3 deaths. Logistic regression showed that aortic valve area and peak VO2 were not significant predictors for clinical events. Conclusion: Our data demonstrates that a significant proportion of patients with apparently asymptomatic aortic stenosis exhibit exercise limitation as measured by peak VO2. Cardiopulmonary exercise testing may provide incremental objective evidence of early deterioration, over and above parameters obtained from conventional treadmill testing, as suggested by current guidelines. Conflict of Interest: nil